The Role of Problem-Based Mufradat Learning on “ISMU fil Arabia” Activity - Muhammad Kusuma Wardhana; Mamluatul Hasanah; Syaiful Mustofa (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2026)
Nativism has been a pessimistic topic when discussing its implementation in the context of children's education. This happens because the flow of its universal ability, which has been carried since birth, is not influenced by external elements like an Arabic language environment gifted by teacher value. In fact, the understanding of Nativism is not that shallow; there are several indicators that are missed when looking at implicit phenomena in the role of Arabic language acquisition without involving this understanding. Using a phenomenological approach related to the